2015
DOI: 10.1039/c5tc01074h
|View full text |Cite
|
Sign up to set email alerts
|

Study on the internal field and conduction mechanism of atomic layer deposited ferroelectric Hf0.5Zr0.5O2 thin films

Abstract: The internal field (E int ) in ferroelectric films is an important factor which can affect the reliability of practical devices utilizing two memory states which results from the remanent polarizations of ferroelectric films. In the current work, the E int in TiN/Hf 0.5 Zr 0.5 O 2 /TiN capacitors was controlled by changing the annealing atmosphere (N 2 , O 2 , and forming gas). The magnitude of negative E int in O 2 -annealed samples was the largest, whereas that in the forming gas-annealed sample was the smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 54 publications
4
64
0
Order By: Relevance
“…Thus, the difference in ε r value might be determined by the relative fractions of the tetragonal and orthorhombic phases or the defect concentration, which is expected to decrease the average dielectric constant with local lattice distortions. The ε r value of the tetragonal phase (35)(36)(37)(38)(39)(40) was higher than that of the orthorhombic phase (25)(26)(27)(28)(29)(30). Thus, the high ε r value of TEMA HZO capacitor indicates that it has a higher tetragonal phase fraction compared to the TDMA HZO capacitors.…”
Section: Resultsmentioning
confidence: 86%
“…Thus, the difference in ε r value might be determined by the relative fractions of the tetragonal and orthorhombic phases or the defect concentration, which is expected to decrease the average dielectric constant with local lattice distortions. The ε r value of the tetragonal phase (35)(36)(37)(38)(39)(40) was higher than that of the orthorhombic phase (25)(26)(27)(28)(29)(30). Thus, the high ε r value of TEMA HZO capacitor indicates that it has a higher tetragonal phase fraction compared to the TDMA HZO capacitors.…”
Section: Resultsmentioning
confidence: 86%
“…From the spectra, it could be confirmed that the formation of a stable monoclinic phase was inhibited, and only the diffraction peaks of the tetragonal phase (t‐phase, space group: P 4 2 / nmc ) or the orthorhombic phase (o‐phase, space group: Pca 2 1 ) were observed for all films. The successful fabrication of a Pt/TiN/Hf x Zr 1− x O 2 /TiN capacitor could be confirmed from the TEM images . The Hf x Zr 1− x O 2 films were crystallized during a rapid thermal annealing process.…”
Section: Electrocaloric Characteristics Of Various Thin‐film Materialsmentioning
confidence: 77%
“…In the case of the ferroelectric Hf 0.5 Zr 0.5 O 2 films, a 150‐time field cycling with a 3.26 MV cm −1 pulse height and a 1 kHz frequency was performed before the P – E measurements to rule out a polarization increase due to the wake‐up effect . The P r value of the woken‐up state was as large as the values in the literature . This is abnormal behavior because the polarization of ferroelectrics generally decreases with increasing temperature, resulting in a positive ECE.…”
Section: Electrocaloric Characteristics Of Various Thin‐film Materialsmentioning
confidence: 93%
“…The ferroelectricity in HfO 2 films originates from the existence of the metastable and non-centrosymmetric orthorhombic phase with the space group of P ca2 1  1415. If crystallization occurs under mechanical encapsulation, the formation of the monoclinic phase is inhibited10, then the orthorhombic phase that shows a distinct piezoelectric response141617181920 will obtained. It is 600 ~ 700 °C for HfO 2 films crystallized according to previous reports21.…”
Section: Resultsmentioning
confidence: 99%